EDUCATION ANTI-CORRUPTION IN INDONESIA: PROBLEMS, CHALLENGES AND SOLUTIONS - Alwan Hadiyanto (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Nowdays corruption has been being a culture.Corruption has poisoned almost all institution not only public but also private institutions and become prevalent when we watch it on television every day. People are not surprised when they know or watch on television that some leaders of this country have committed corruption. Corruption has spread out endemicly and systemically. However, if we look back on the first process of corruption, it may be concluded that education isthe main factor of corruption. Education actually starts from family, then school, and the society must collectively perform a civilizing fair and honest behavior, or in other words anti-corruption education. It must be implemented to reduce this endemic problem. It needs a national movement to implement the anti-corruption education and it starts from education. Based on the above background, the author formulated the problem as follows. 1) How is the implementation of anti-corruption education in Universityeducation? 2) How is the important role of early anti-corruption education in preventing corruption? 3) What is the obstacle and effort in combating corruption? This study is based on a normative juridical approach, because this study is the legal research doctrinaire which is also known as library research or document studieswhich is only done or shown the written rules or other legal materials. Anti-corruption education becomes very important as the systematic and massive efforts in building a new civilization of education. Education is a guidance for young people and one of good idea in this corruption case is the implementation of anti-corruption education in the nation character education in Indonesia. Keywords: Education, Anti-Corruption